Meneropong Gebrakan Paus Fransiskus Dalam Hukum Gereja - Yohanes Servatius Lon; Fransiska Widyawati (Jurnal Pendidikan dan Kebudayaan Missio, 2023)
As the leader of the Catholic Church, Pope Francis has made many changes in the life of the Catholic Church, including in Church Law. He is known as a revolutionary and progressive pope for changing various traditions in the Catholic Church. However some of his policies have generated controversy and been the subject of public debate within and outside the Church itself. Using a literature study, this paper highlights changes in marriage law, lay involvement, liturgy, Church unity, and Church sanctions. This study finds that the changes made by the Pope aim to strengthen the mission of the Church to present the merciful face of God, ensure that there is justice for all people in enjoying the grace of salvation, and increase the laity’s participation in Church life. Controversy and public debate that arose as a result of Pope Francis' policies were actually a consequence of his efforts to defend the Church's doctrine in the midst of increasingly strong world challenges demanding the upholding of human rights for everyone. This study concludes that the changes that occur are a part of history that the Church must face today.